Facile Synthesis of Composite Chitosan and Durio zibethinus Seed and Its Applications as Adsorbent of Metal Ion Ni(II) - Silvia Devi Eka Putri; Sri Mulijani; Komar Sutriah (UNIVERSITAS SEBELAS MARET (UNS), 2023)
Nickel is one of the most dangerous heavy metals that impact water ecosystems and human health. In the study, natural and harmless composite materials such as biochar and chitosan were modified to build adsorbent composites and form optimal conditions for the adsorption of nickel heavy metal ions from contaminated wastewater. Biochar was prepared from Durio zibethinus seeds by hydrothermal method to form nanopowder. It was treated with acid, while chitosan was designed as nanopowder by hydrothermal method, also without acid treatment. Composite adsorbents were prepared by mixing biochar and chitosan with a ratio of 4:3 (w/w). Fourier Transform Infrared characterizes composite materials as adsorbents, biochar, and chitosan. The surface morphology of the adsorbent was evaluated by scanning electron microscopy. Furthermore, Langmuir, Freundlich, and Temkin isotherms determine the adsorbent's performance. In addition, batch adsorption experiments were carried out to measure the effect of solution pH, adsorbent dosage, and initial concentration of metal ions. Nickel ion adsorption by the composite adsorbent showed an adsorption capacity of 26.69 mg/g, a maximum removal efficiency of 89.39% at optimum conditions of pH 6, an adsorbent dose of 0.5 g, and a contact time of 200 minutes. This adsorption capacity was better than chitosan and durian seed adsorbents. The nickel ion adsorption process by composite adsorbent shows a pattern in the Temkin isotherm model. In contrast, the chitosan and Durio zibethinus seed adsorbents tended to follow the Langmuir and Freundlich isotherm models. In addition, the adsorption kinetics of the composite material showed pseudo-second-order kinetics, and the reaction was exothermic.